2011
DOI: 10.1029/2011ja016794
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric V-shaped streaks recorded on board DEMETER satellite above powerful thunderstorms

Abstract: [1] We report here observations of both symmetric and asymmetric forms of V-shaped streaks on VLF spectrograms recorded on board the DEMETER satellite. Recent investigations have shown that V-shaped streaks are associated with intense and numerous 0+ whistlers generated in the VLF range by active thunderstorms. To understand the origin of the different spectral forms of the V-shaped events, a systematic survey of these phenomena is performed by means of a visual inspection of the VLF spectrograms covering more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In a more detailed spectrogram, one can recognize that the event is formed by lightning‐generated spherics attenuated at specific, smoothly varying frequencies. Rather similar events were reported by Parrot et al () and El‐Lemdani Mazouz et al (). These events, with a striking V‐shaped signature, were usually observed in the very proximity of intense thunderstorms.…”
Section: Introductionsupporting
confidence: 89%
“…In a more detailed spectrogram, one can recognize that the event is formed by lightning‐generated spherics attenuated at specific, smoothly varying frequencies. Rather similar events were reported by Parrot et al () and El‐Lemdani Mazouz et al (). These events, with a striking V‐shaped signature, were usually observed in the very proximity of intense thunderstorms.…”
Section: Introductionsupporting
confidence: 89%
“…We also develop a simple model of the event formation, and we demonstrate its performance for two selected events. Parrot et al [2008] and Mazouz et al [2011] reported curious events observed by the DEMETER spacecraft whose form in the frequency-time spectrograms resembled a V-shaped signature. They occurred at times when the satellite was passing above regions with a strong lightning activity (tens of lightning strokes per second), and they were shown to be related to the propagation of lightning-generated waves in the Earth-ionosphere waveguide prior to their leakage to the DEMETER altitudes (about 700 km).…”
Section: Introductionmentioning
confidence: 99%